2003
DOI: 10.1080/0144619032000056144
|View full text |Cite
|
Sign up to set email alerts
|

Organizational motivation and inter-organizational interaction in construction innovation in Singapore

Abstract: This paper examines the individual firm's motivation to adopt innovation in a construction project, and the inter-organizational interactions of relevant parties involved in innovation. Based on the theory of organizational motivation and inter-organizational relationships, seven hypotheses are set out. These hypotheses are tested using a structured questionnaire, and data were collected via a postal survey. From the results, it is concluded that an innovative proposal may be successfully implemented in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 15 publications
9
99
1
Order By: Relevance
“…The response rate of 20.9 percent is not uncommon and acceptable and is in line with the opinions of Akintoye (2000) and Dulami et al, (2003). They reported that the norm response rate in the construction industry for postal questionnaires is around 20-30 percent.…”
Section: Response Ratesupporting
confidence: 64%
“…The response rate of 20.9 percent is not uncommon and acceptable and is in line with the opinions of Akintoye (2000) and Dulami et al, (2003). They reported that the norm response rate in the construction industry for postal questionnaires is around 20-30 percent.…”
Section: Response Ratesupporting
confidence: 64%
“…Once the project objectives are met, KPIs are used to evaluate the project's success. The project impacts, outcomes, outputs, and inputs can be clarified and linked by the use of indicators; problems that may slow down the progress of the project can also be highlighted (Effective Implementation: Key to Development Impact, September, 1992).…”
Section: Performance Indicatorsmentioning
confidence: 99%
“…A sample of 120 organisations were electronically emailed questionnaires in the UK with 69 responses thus signifying a response rate of 57.5% which is in line with the views of Akintoye [29] and Dulami et al [30]. The adoption of stratified random sampling allowed the researchers more control over the eventual sample to ensure it reflected the makeup of the overall population whilst also minimising the possibility by bias by ensuring every item of the population had an equal probability of being selected [31].…”
Section: Methodsmentioning
confidence: 77%